The Triatominae (Hemiptera: Heteroptera: Reduviidae) of Veracruz, Mexico: geographic distribution, taxonomic redescriptions, and a key - Sandoval-Ruiz, César Antonio; Cervantesperedo, Luis; Mendoza-Palmero, Fredy Severo; Ibáñez-Bernal, Sergio (Zootaxa, 2012)
An annotated list of the triatomine bugs from Veracruz, Mexico, is presented. The list is mainly based on field collections, but also on literature review and museum collections. Ten species in five genera and two tribes are known in the state. Two species, Triatoma dimidiata (Latreille), the most common and widely distributed, and Triatoma gerstaeckeri (Stål), are the most important vectors of Chagas disease in the region. Panstrongylus rufotuberculatus (Champion), Belminus costarricensis Herrer, Lent & Wygodzinsky, and Eratyrus cuspidatus (Stål) are confined to sylvan habitats in the south of the state. Triatoma rubida (Uhler) probably represent a misidentification. The presence of Meccus pallidipennis Stål, Panstrogylus geniculatus (Latrielle), Triatoma barberi Usinger, and Triatoma infestans (Klug) are fortuitous. GARP distribution maps are provided for T. dimidiata and T. gerstaeckeri. A key to species and photographs of the adults of the ten species are also included.